Conversion of Cyclohexanones to Alkyl Aryl Ethers by Using a Pd/C–Ethylene System. Issue 2 (13th January 2017) - El‐Deeb, Ibrahim Yussif; Tian, Miaomiao; Funakoshi, Tatsuya; Matsubara, Ryosuke; Hayashi, Masahiko
Abstract : The conversion of cyclohexanone and substituted cyclohexanones into alkyl aryl ethers by using a Pd/C–ethylene system is discussed, with ethylene functioning as a hydrogen acceptor. The ether products are easily transformed into the corresponding phenols by treatment with BBr3 . The direct conversion of cyclohexenone into phenol in the presence of a catalytic amount of Pd/C under an ethylene atmosphere is also described. Abstract : The conversion of cyclohexanone and substituted cyclohexanones into alkyl aryl ethers by using a Pd/C–ethylene system is disclosed. The ether products are easily transformed into the corresponding phenols by treatment with BBr3 . The direct conversion of cyclohexenone into phenol is also described.